The moderating role of organizational culture on the relationship between workers’ attitudes towards telework and happiness - Junça Silva, A.; Coelho, N. (Kybernetes, 2023)
The COVID-19 pandemic forced organizations to adopt telework, many of them without any prior preparation, influencing not only daily organizational routines, but also workers’ happiness. Happiness is important for organizations because happy and fulfilled workers are a key to achieve organizational success. Organizational culture is a critical factor to implement telework, because it may influence the workers’ attitudes toward this model of work and their happiness. This study aimed to test the moderating role of organizational culture (clan, adhocracy, market, hierarchical) in the relationship between attitudes toward teleworking and happiness. To meet the objectives, we collected data from 265 teleworkers. The results revealed that only market culture moderated the relationship between attitudes toward teleworking and happiness, such that this relationship became stronger in the presence of a goal-oriented culture. No other dimension of organizational culture significantly moderated the relationship between telework and happiness. These results prove to be fundamental for a better understanding of organizational and individual factors when organizations want to implement telework as a work arrangement. Considering the mainstream literature in telework, to the best of the authors’ knowledge, this is the first study to date to integrate the moderating role of organizational culture in the relationship between telework and happiness.